2017
DOI: 10.1051/shsconf/20173403004
|View full text |Cite
|
Sign up to set email alerts
|

Value Relevance of available-for-sale financial instruments (AFS) and revaluation surplus of PPE (REV) components of other comprehensive income

Abstract: Abstract.Value relevance studies have thus far provided mixed evidence. Studies also found that fair value reporting has a significant impact on the value relevance of other comprehensive income. Additionally, most studies on value relevance of other comprehensive income focused on developed countries where the capital market is more efficient. In these settings due to the existence of active market, fair valuation of assets may not pose a major problem. In Malaysia the mandatory reporting of comprehensive inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…Pinto (2005) also found that the OCI component in the form of foreign currency translation adjustments had value relevance for a sample of companies in America between 1991 and 1996. The relevance of the OCI value after the mandatory presentation of OCI was also found by Yousefinejad, Ahmad, & Embong (2017) and Park (2018).…”
Section: Previous Research Reviewmentioning
confidence: 65%
“…Pinto (2005) also found that the OCI component in the form of foreign currency translation adjustments had value relevance for a sample of companies in America between 1991 and 1996. The relevance of the OCI value after the mandatory presentation of OCI was also found by Yousefinejad, Ahmad, & Embong (2017) and Park (2018).…”
Section: Previous Research Reviewmentioning
confidence: 65%
“…Regarding the relevance of financial assets available for sale, in line with some previous research, the pension benefit program items are in contrast to previous research outside of Indonesia. In Australia, the most relevant OCI item is cash flow hedges (Banks et al, 2018), as well as in America (Rees & Shane, 2012), in Iran the most relevant is the revaluation of fixed assets (Steinberg & Forscher, 2014), in Canada is the profit loss of financial assets (Kanagaretnam et al, 2009) and in Malaysia are the profit loss of financial assets and asset revaluation (Yousefi Nejad & Ahmad, 2017).…”
Section: Discussion Of Results Of the Researchmentioning
confidence: 99%
“…Meanwhile, other studies concluded that OCI has low predictive power in estimating future net income and future cash flow, NI is more predictive than OCI (Jones & Smith, 2011). Although the difference is not significant, NI is more predictive in assessing stock price changes compared to OCI (Kubota et al, 2011;Yousefi Nejad & Ahmad, 2017;Humayun Kabir & Laswad, 2011;Kanagaretnam et al, 2009); Būmane, 2018), Steinberg & Forscher, 2014. That means, NI is more predictive than OCI because NI is a real income that has been realized, whereas OCI has not been realized due to changes in fair value and volatility in market conditions (not due to managerial performance results).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Those studies do not provide a consensus on accounting quality of OCI. For instance, while Devalle and Magarini (2012), Veltri and Ferraro (2018) and Caliskan (2019) report no evidence for accounting quality of OCI, Mechelli and Cimini (2014), Yousefinejad et al (2017) and Park (2018) conclude the opposite outcome. In a single study, Goncharov and Hodgson (2011) find evidence for accounting quality of OCI in 9 out of 16 analysed jurisdictions.…”
Section: Literature Reviewmentioning
confidence: 99%